Educar para la Paz a partir de la Deconstrucción de las Violencias del Sistema Educativo - Sofía Herrero-Rico (Revista de Cultura de Paz)
Introduction: This article reassesses the need to educate for peace in the societies impregnated with violence that we have established. In this endeavor, it looks at the violence that the educational system reproduces as a social subsystem.